EXTRAORAL RADIOGRAPHY: AN ALTERNATIVE TO INTRAORAL RADIOGRAPHY FOR ENDODONTIC (ROOT CANAL SYSTEM) LENGTH DETERMINATION - Zafar, Muhammad Sohail; Javed, Ejaz (European Scientific Journal, ESJ, 2013)
The objective of this study was to evaluate the accuracy of extraoral radiographic technique for determination of the working length and to determine the magnification error. This technique can be an additional supplemental tool that can be utilized as a reliable alternative for the intraoral periapical radiographs. Eighty-five mandibular premolars were selected using convenience sampling. Medical & dental history of the patients was taken. The teeth were anesthetized and root canals were accessed, irrigated and dried. A file was cemented into the canal using Glass Ionomer Cement and handle was cut from the tooth reference point followed by extraoral radiograph taken by placing cone at -35 angles. Tooth was extracted to determine actual length and comparing with radiographic length. The ethical approval was obtained from the research ethics committee of the college.The accuracy of extraoral radiography is 94.5 + 4.43% and magnification error (5.5 + 4.3%) is not significant statistically. Extraoral radiographs (86 %) determined average tooth length precisely with magnification error of less than 10 %. The mean difference between the actual length and the extraoral radiographic length is 6.1 ± 5.1 % of the actual length. The extraoral radiography is a valuable technique that is reliable (accuracy 94.6 ± 4.3% for measuring working length), useful and affective technique for clinical dentistry and endodontic working length determination particularly where use of intraoral radiography is difficult or impossible.